Implementing an Online Longitudinal Leadership Development Program Using a Leadership-Specific Continuing Professional Development (CPD) Tool - Grace Oyenuga; Miranda Law; Minesh Parbat; Toyin Tofade (MDPI AG, 2020)
As the roles of a pharmacist continue to evolve, leadership is an imperative skill for pharmacists to advance in their profession. To advance leadership behaviors, a number of tools, programs, and services have been developed worldwide to encourage the use of these behaviors in practice. A brief summary of different leadership opportunities around the globe are provided. A continuing professional development process and tool for developing and mentoring leaders that are ready to take the next step in their growth journey is introduced. This tool can be used in a live or online setting and is amenable to a longitudinal environment for leadership development and mentoring. A detailed process for implementing an online leadership development program and opportunities for future development are also described. While leadership skills can be developed in many ways, it is still unclear which methods and tools are the most effective in training pharmacists to maximize their leadership abilities. Additional research on effectiveness and impact of tools and processes for development are needed. Individuals and organizations are encouraged to consider implementing easily accessible leadership development and mentoring programs to advance the leadership skills of interested individuals.